A Comparative Study: Modisco and Acupressure for Weight Gaining Toddler - Hesty Widowati; SMF Hanum; Herista Novia Widanti; Mar`Ati Amalia Rizqiyah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: Inappropriate practice of feeding and complementary foods is one of the causes of malnutrition in children in Indonesia. Providing additional food such as Modisco (Modified Dietetic Skimmed Milk and Coconut Oil) can be an effort to improve the nutritional status of toddlers, besides acupressure therapy can increase appetite so that it can increase the child's weight.Objective: This study aims to determine the difference in the effectiveness of the combination of Modisco and acupressure with only Modisco on increasing toddler’s  weight.Methods: This study used a Quasy Experiment group design with a Pre and Post Test Control Group Design approach. The inclusion criteria were children aged 1-5 years, included in the thin category and did not have heart, liver, and kidney disease. The sample was selected by purposive sampling as many as 30 toddlers who were divided into 2 groups with the provision that group I amounted to 15 toddlers were given complementary foods made from modisco II for 14 days and acupressure 6 times (2 times a week for 3 weeks), while group II amounted to 15 toddlers are only given complementary foods made from modisco II for 14 days. Statistical test using Paired sample T Test.Results: In group I, there was a difference in the average weight of children under five before and after the intervention with p value = 0.001 (p < 0.005), meaning that the combination of modisco and acupressure can increase body weight in toddlers. In group II, there was a difference in the average weight of children under five before and after the intervention with a p value = 0.003 (p < 0.005), which means that modisco can increase body weight in toddlers.Conclusion: From the results of the difference in the average weight of group I and group II with a value of p = 0.013, it means that there is no significant difference between the groups given the combination of modisco plus acupressure and the modisco group on the weight gain of toddlers.